Memory Modulation Via Non-invasive Brain Stimulation: Status, Perspectives, and Ethical Issues - Farina, Mirko; Lavazza, Andrea (Frontiers in Human Neuroscience, 2022)
While research to improve memory or counter decay caused by neurodegenerative diseases has a fairly long history, scientific attempts to erase memories are very recent. The use of non-invasive brain stimulation for memory modulation represents a new and promising application for the treatment of certain disorders [such as Post-Traumatic Stress Disorder (PTSD)]. However, numerous ethical issues are related to memory intervention. In particular, the possibility of using forms of non-invasive brain stimulation requires to distinguish treatment interventions from the enhancement of the healthy. Furthermore, a range of important societal and legal concerns arise when manipulating memories. In this short contribution, we address some of the most significant ethical, social, and legal implications surrounding the application of memory-modulation techniques and offer a series of reflections and considerations, which we hope can be of use to guide -and perhaps regulate- their potential, future implementation in society.